Otac, sin, sveti duh - Gvardiol, Zelimir (Germany : Spesfilm, 1998)
A three-part documentary, "Father, A Son, A Holy Ghost" is a social and anthropological examination of the aftermath of the war in former Yugoslavia. Three children, three stories of war and the traumas it leaves behind. Part one is the story of a twenty-year-old boy, a deserter of the war in Bosnia and Herzegovina who finds himself taking on the care of his half sisters and half brother after his stepmother is killed by the common father. Part two is the story of a sixteen year old whose life has been traumatized by both the divorce of his parents and the ensuing war. Part three is the story of an unborn child deprived of health as a war breaks out just before his birth, a war that claims the life of his father and forces his mother to give birth in a ditch.
Keywords: Documentary films